GIS - Based Surface Water Irrigation Potential Assessment of Muga Watershed, Abbay Basin, Ethiopia - Assefa, Natnael Yasab (International Journal of Scientific Research in Civil Engineering, 2020)
Although Muga watershed has a large potential to develop surface irrigation, only 0.3% of the 73815.37 hectares (ha) potentially available has been developed. To examine the underlying causes of this lack of irrigation development, this study evaluates the suitability of surface water irrigation for the Muga watershed, Abbay Basin, Ethiopia. Surface water availability and land potentially suitable for irrigation development were considered. Surface water potential for ungauged each sub-watershed was simulated by using SWAT model, the performance of SWAT model was checked by SWAT-CUP model. Land suitable for surface irrigation was determined with a GIS-based multi-criteria evaluation, which considers the interaction of various factors such as climate, distance from water supply (sources), soil type, land cover, slope. The surface irrigation suitability analysis of these factors indicates that 70.64 % of soil and 66.63 % slopes in the study area are suitable for surface irrigation system. In terms of land cover/use evaluation, 72.43% of land cover/use is suitable for surface irrigation and 200m Euclidian distance was considered. The result of weighted overlay analysis indicates that, 8.408 % Muga watershed is suitable for surface irrigation. To grow on these identified irrigable areas, five crops such as maize, lentils ,tomato ,potato and cabbage were selected and their irrigation demand calculated by using CROPWAT model. The maximum crop water requirement for selected crop is 3.95m3/s with the coverage areas 2172.2295ha. The amount of flow in Muga river in the same crop period is 12.417 m3/s. Total surface irrigation potential of the study area was obtained as 6206.37 ha. The result indicated that Stream flows are much larger than their command area monthly irrigation demand. This implies that surface irrigation potential of these rivers limited by the land area to be irrigated along them. The irrigation potential of this study area can be increased by using sprinkler and drip irrigation methods.